2013
DOI: 10.1371/journal.pone.0074745
|View full text |Cite
|
Sign up to set email alerts
|

An Innovative Cascade System for Simultaneous Separation of Multiple Cell Types

Abstract: Isolation of different cell types from one sample by fluorescence activated cell sorting is standard but expensive and time consuming. Magnetic separation is more cost effective and faster by but requires substantial effort. An innovative pluriBead-cascade cell isolation system (pluriSelect GmbH, Leipzig, Germany) simultaneously separates two or more different cell types. It is based on antibody-mediated binding of cells to beads of different size and their isolation with sieves of different mesh-size. For the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Whereas the microbead method enables isolation of purified PMNs in sufficient quantity, viability and without pre-activation, the 3D-µ-slide facilitates high-quality microscopy, linear concentration gradients and support of long-term assays. [7][8][9]…”
Section: Introductionmentioning
confidence: 99%
“…Whereas the microbead method enables isolation of purified PMNs in sufficient quantity, viability and without pre-activation, the 3D-µ-slide facilitates high-quality microscopy, linear concentration gradients and support of long-term assays. [7][8][9]…”
Section: Introductionmentioning
confidence: 99%
“…In order to study the correlation of CD133 and/or EpCAM with malignant features of MDA-MB-231, a magnetic step-by-step cell isolation with antibodies directed against the two surface antigens was performed. Since CD133 + cells are rare elements in the MDA-MB-231 cell population, we applied the MACS technique instead of the currently used Fluorescence-Activated Cell Sorting, thus ensuring the achievement of a relatively high number of cells in a short time [ 17 , 23 ]. We obtained populations enriched in CD133 − /EpCAM − , CD133 − /EpCAM + , CD133 + /EpCAM − or CD133 + /EpCAM + cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…MDA-MB-231 sub-populations enriched in CD133 + and/or EpCAM + cells were obtained by means of the MACS immunomagnetic separation system, essentially as described by Pierzchalski et al [ 23 ]. In particular, cells were firstly labeled with CD133/1 MicroBeads (Miltenyi Biotech) and subjected to positive magnetic cell separation through MACS SD columns in the field of the MACS magnet (Miltenyi Biotech), according to manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…A weak point in the study is that we did not test viability of the harvested stem cells. Pierzchalski et al (10) reported that high cell numbers can be isolated by this method. Positive selection, by labeling the target cells, is the fastest and the most efficient way to isolate a cell subset with high purity and Stem cell separation from cord blood @ C I C E d i z i o n i I n t e r n a z i o n a l i yield, but because separation is based on a single parameter (i.e., magnetization), this method is generally effective only for the isolation of a single cell population.…”
Section: Discussionmentioning
confidence: 99%